PROMOTION SYSTEM FOR PROMOTIONAL PRODUCTS AND TOURIST OBJECT IN PATUK GUNUNGKIDUL DISTRICT - Yuliani Indrianingsih; Astika Ayuningtyas; Uyuunul Mauidzoh (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2020)
Patuk District is a gateway to enter Gunungkidul Regency. In Patuk District there are several tourist attractions such as Kampoeng Emas, Purba Volcano and Embung Nglanggeran. In addition, there is also the potential for processed food products from natural and agricultural products in Patuk District. Leading potentials in Patuk District need to be promoted to the wider community so that they are known and can be an attraction for tourists. The purpose of this research is to design and create a system of promotion of superior products and Web-based tourism objects that can facilitate Patuk District in introducing superior products owned by each village and facilitate the general public to obtain superior product information in Patuk District. The method used in the analysis and system design uses Unified Modeling Language (UML). In this study, a system consisting of three users was produced, namely admin in the Inter-Village Coordination Board (BKAD), admin of business owners and general users. This system can be accessed at the address www.jelajahipatuk.com.